2010
DOI: 10.1007/s11881-010-0040-y
|View full text |Cite
|
Sign up to set email alerts
|

Are preservice teachers prepared to teach struggling readers?

Abstract: Reading disabilities such as dyslexia, a specific learning disability that affects an individual's ability to process written language, are estimated to affect 15-20% of the general population. Consequently, elementary school teachers encounter students who struggle with inaccurate or slow reading, poor spelling, poor writing, and other language processing difficulties. However, recent evidence may suggest that teacher preparation programs are not providing preservice teachers with information about basic lang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
111
4
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 131 publications
(147 citation statements)
references
References 35 publications
(57 reference statements)
18
111
4
1
Order By: Relevance
“…The analysis also showed that there is much common variance shared by knowledge related variables (KPA, KFVC and KASSI) in the prediction of global perceived knowledge, and that there are suppression effects between variables. Although these results are similar to those found by others (e.g., Binks-Cantrell et al, 2012;Washburn et al, 2011), the large overlap between KPA, KFVC and KASSI, suggests that these variables represent one single factor. It seems therefore meaningless to explain the predictive value of any specific knowledge variables.…”
Section: Discussionsupporting
confidence: 91%
“…The analysis also showed that there is much common variance shared by knowledge related variables (KPA, KFVC and KASSI) in the prediction of global perceived knowledge, and that there are suppression effects between variables. Although these results are similar to those found by others (e.g., Binks-Cantrell et al, 2012;Washburn et al, 2011), the large overlap between KPA, KFVC and KASSI, suggests that these variables represent one single factor. It seems therefore meaningless to explain the predictive value of any specific knowledge variables.…”
Section: Discussionsupporting
confidence: 91%
“…Variable results were also reported by Bos et al (2001) who found that "Whereas more than 50 percent of the preservice and inservice teachers were able to segment the phonemes in a two-phoneme word, they were unable to do this for more complex four-phoneme words." (p.114), and Washburn et al (2011) who reported that, as a group, preservice teachers had a varied range of knowledge concerning these basic skills. This variability might be explained by the way in which this knowledge was assessed.…”
Section: Discussionmentioning
confidence: 99%
“…Surveys designed by Al Otaiba, Lake, Greulich, Folsom and Guidry (2012), Binks-Cantrell, Joshi and Washburn (2012), Bos, Mather, Dickson, Podhajski and Chard (2001), Babur (2001), Moats, (1994), and Washburn, Joshi and Binks-Cantrell (2011) provided the basis for the development of the survey. Author-developed questions on spelling mirrored the existing items on reading.…”
Section: Surveymentioning
confidence: 99%
“…Teacher knowledge, however, is critical for the teaching of reading, including for those children who struggle with reading (Washburn et al, 2011). As such, this research study aimed to evaluate whether a targeted online approach to teaching phonological awareness and orthographic knowledge for preservice teachers was successful in improving their skills in these areas during their first year of study.…”
Section: Brief Review Of the Literature The Teaching Of Readingmentioning
confidence: 99%